Adoption of Orange-Fleshed Sweetpotato (OFSP) technologies in Southern Ethiopia - Tenaye, A.; Gebeyehu, S.; Cherinet, M. (MDPI, 2025)
Addressing malnutrition and vitamin A deficiency in Ethiopia necessitates innovative, food-based solutions such as biofortified crops. This study assesses the adoption rates of Orange-Fleshed Sweetpotato (OFSP) and examines the factors influencing adoption among project participants, non-participants, and counterfactual households in the former Southern Nations, Nationalities, and Peoples’ (SNNPs) region. Primary data were collected in 2023 through a survey of 990 households across six districts, and logistic regression was employed to identify key determinants of adoption. The findings reveal OFSP adoption rates of 53% among participants, 56% among non-participants, and 42% among counterfactual households, with significant variation across regions. Factors positively influencing adoption include household education, proximity to health centers and OFSP multiplication sites, frequent extension contact, and access to agricultural services. This study underscores the potential of newly released OFSP varieties to enhance food security and resilience in malnutrition-prone areas. The comparable adoption rates between participants and non-participants highlight significant spillover effects from long-term interventions, suggesting widespread community benefits. However, the limited adoption of complementary OFSP package components points to the need for enhanced training programs and streamlined technology dissemination strategies. These findings contribute to understanding how biofortified crops can be scaled effectively to improve food security and nutrition, offering valuable insights for policy and program design.